“This is a public service announcement... with guitar!” Le frontiere dell'impolitico e la musica nella letteratura contemporanea (Altre Modernità, 2018)
Although the characters of Izzo’s Total Khéops do not belong to any political organisation, their gestures, even if in a peculiar way, may be referred to as political. Similarly, the subcultural groups depicted in King’s Skinheads and Santoni’s Muro di casse deploy a series of everyday practices, political as well, which are completely different from the ones expressed by the ballots. Analysing the strategies of focalization used within these novels, this essay aims at describing how the personal involvement into subcultures represents a form of resistance against the discipline imposed to the bodies by the capitalist system of production and how it also provides alternative ways of socialization, which allow members of subcultures to question at its core the frontiers of what can or cannot be considered a political act.